The Effectiveness of the Spiritual Treatment Groupon Improving the Quality of Life and Mental Health in Women with Breast Cancer - Abdolmajid Bahreinian; Hamed Radmehr; Hossein Mohammadi; Bita bavadi; Mohammad Reza Mousavi (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objectives: The purpose of this study was to explain Effectiveness of spiritual therapy based on group on increase mental health and quality of life in Women with breast cancer. Materials & Methods: This study is a clinical trial, in a per - post design. 24 patients (women with breast cancer) were randomly selected, and located in the experimental group (n =12) and control group (n =12). Participants in the experimental group (each 90 minutes) received spiritual therapy for 12 sessions. Collection tool data in this study was Symptom Chek List - 90 - Revised (SCL- 90 - R) and Quality of life questionnaire (QLQ). Data were analyzed by using SPSS software and descriptive statistics methods (mean, standard deviation, variance) and inferential statistics (analysis of covariance, analysis of variance, Z, F Levin, KS).In this study, all relevant ethical issues were considered. Results: The findings of this study showed that spiritual therapy based on group has considerable influence on increase mental health and quality of life in women with breast cancer. In other words, this intervention could improve the quality of life and mental health in the experimental group Conclusion:The result of this study showed that spiritual therapy, is known effective source for dealing with physical and psychological response, and This intervention can be used in Common medical treatments to improve the quality of life and mental health  in women with breast cancer. Keywords: Breast cancer, Mental health, Quality of life, Spiritual therapy based on group For downloading the full-text of this article please click here. Please cite this article as: Bahreinian A, Radmehr H, Mohammadi H,BavadiB, Mousavi M. The Effectiveness of the Spiritual Treatment Groupon  Improving the Quality of Life and Mental Health in Women with Breast Cancer. J Res Relig Health. 2017; 3 (1): 64- 78.